Statement on the safety of MON810 maize pollen occurring in or as food - EFSA Panel on Genetically Modified Organisms (GMO) (Wiley, 2011)
Abstract In this statement the EFSA GMO Panel responds to a request from the European Commission on whether data provided within application RX‐MON810 on maize MON810 are sufficient to conclude on the safety of MON810 pollen as or in food and, if it is the case, to confirm MON810 pollen safety. Data on molecular characterisation did not identify features of maize MON810 pollen with a potential to raise any safety concerns. The EFSA GMO Panel has previously assessed the safety of the Cry1Ab protein in MON810 and the assessment and conclusions of the GMO Panel on safety of the protein Cry1Ab (including toxicity and allergenicity) reached for food/feed aspects also apply to pollen. While the EFSA GMO Panel is not in a position to conclude on the safety of maize pollen in or as food in general, it concludes that the genetic modification in MON810 maize does not constitute an additional health risk if MON810 maize pollen were to replace maize pollen from non‐GM maize in or as food.